Hydrogen Peroxide Variation Patterns as Abiotic Stress Responses of Egeria densa - Asaeda, Takashi; Rahman, Mizanur; Liping, Xia; Schoelynck, Jonas (Frontiers in Plant Science, 2022)
In vegetation management, understanding the condition of submerged plants is usually based on long-term growth monitoring. Reactive oxygen species (ROS) accumulate in organelles under environmental stress and are highly likely to be indicators of a plant’s condition. However, this depends on the period of exposure to environmental stress, as environmental conditions are always changing in nature. Hydrogen peroxide (H2O2) is the most common ROS in organelles. The responses of submerged macrophytes, Egeria densa, to high light and iron (Fe) stressors were investigated by both laboratory experiments and natural river observation. Plants were incubated with combinations of 30–200 µmol m-2 s-1 of photosynthetically active radiation (PAR) intensity and 0–10 mg L-1 Fe concentration in the media. We have measured H2O2, photosynthetic pigment concentrations, chlorophyll a (Chl-a), chlorophyll b (Chl-b), carotenoid (CAR), Indole-3-acetic acid (IAA) concentrations of leaf tissues, the antioxidant activity of catalase (CAT), ascorbic peroxidase (APX), peroxidase (POD), the maximal quantum yield of PSII (Fv Fm-1), and the shoot growth rate (SGR). The H2O2 concentration gradually increased with Fe concentration in the media, except at very low concentrations and at an increased PAR intensity. However, with extremely high PAR or Fe concentrations, first the chlorophyll contents and then the H2O2 concentration prominently declined, followed by SGR, the maximal quantum yield of PSII (Fv Fm-1), and antioxidant activities. With an increasing Fe concentration in the substrate, the CAT and APX antioxidant levels decreased, which led to an increase in H2O2 accumulation in the plant tissues. Moreover, increased POD activity was proportionate to H2O2 accumulation, suggesting the low-Fe independent nature of POD. Diurnally, H2O2 concentration varies following the PAR variation. However, the CAT and APX antioxidant activities were delayed, which increased the H2O2 concentration level in the afternoon compared with the level in morning for the same PAR intensities. Similar trends were also obtained for the natural river samples where relatively low light intensity was preferable for growth. Together with our previous findings on macrophyte stress responses, these results indicate that H2O2 concentration is a good indicator of environmental stressors and could be used instead of long-term growth monitoring in macrophyte management.